Textual features of legal texts in the domain of commercial law - Więcławska, Edyta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The contribution discusses the characteristics of English legal texts in the context of their communicative function which is manifested by their illocutionary force grounded in their textual structure. The aim here is to verify the thesis that there is a significant degree of structural similarity in legal texts belonging to the same legal genre, which is reflected in the specific layout of the texts, their repetitive structures and recurring linguistic expressions. From the point of view of pragmatics the specific textual features of the texts making up the corpus make it possible to identify legal speech acts which carry illocutionary force referring the performative aspect of legal communication. The said illocutionary acts operate within the text or, more specifically, within its various parts which are discussed in the context of the felicity conditions and grammatical markers of the speech acts. The discussion is based on examples extracted from a corpus made up of authentic texts in the domain of commercial law.
Keywords: illocutionary force; performatives; legal speech acts; communicative function